Hysterectomy for Cervical and Intraligamental Fibroids - Hiramatsu, Yuji (The Surgery Journal, 2020)
Hysterectomy for cervical and intraligamental fibroids is particularly likely to cause massive bleeding, ureteral/bladder injury, and intestinal damage. In such cases, preoperative evaluation is very important, and the way in which surgery proceeds should be based on the preoperative evaluation findings. In other words, before starting surgery, it is important to discuss what second and third methods to use if the first surgical method is unsuccessful. The main points to consider during surgery are expanding the operative field, approaching the operation from a site with weak adhesions, and performing applied techniques such as myomectomy and retrograde hysterectomy.
Keywords: uterine cervical fibroma; intraligamental fibroma; hysterectomy; retrograde hysterectomy; myomectomy